The public television’s problems in the post communist states - Draganov, Ivan (Yearbook Telecommunications, 2016)
Purpose: The development of public TV stations most clearly reveals that in Europe the state tends to withdraw from a lot of its duties and concede them to society. How does that actually happen in post communist countries? Results: The main problems are the lack of political culture, political will for liberalization of the electronic media and desire for honest public debate. Contributions: We can say that for the political fairness of public electronic media, we need honesty and responsibility from each and every journalist. The key problem is whether the political and social situation allows such discourse in electronic media, which is crucial for democracy itself.